2019
DOI: 10.4269/ajtmh.19-0061
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tuberculosis in Women: A Systematic Review

Abstract: Breast tuberculosis (TB) is rarely reported and poorly described. This review aims to update the existing literature on risk factors, clinical presentations, constitutional symptoms, diagnostic procedures, and medical and surgical treatments for breast TB. In all, 1,478 cases of breast TB were collected. Previous history of TB was reported in 19% of cases. The most common clinical appearance of the lesion was breast lump (75%). The most common associated finding was axillary lymphadenitis (33%) followed by sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(69 citation statements)
references
References 140 publications
4
60
2
3
Order By: Relevance
“…(2,5) Lactation was found positive in 7-35% in various studies and it was 21% cases in this study but pregnant or HIV patients were not found. History of TB was reported in 19% of cases of BTB in literature and in this study it was 10.5% (1,6) suggesting that history of tuberculosis should be considered during evaluating breast lump.…”
Section: International Journal Of Medical and Biomedical Studies (Ijmmentioning
confidence: 47%
See 3 more Smart Citations
“…(2,5) Lactation was found positive in 7-35% in various studies and it was 21% cases in this study but pregnant or HIV patients were not found. History of TB was reported in 19% of cases of BTB in literature and in this study it was 10.5% (1,6) suggesting that history of tuberculosis should be considered during evaluating breast lump.…”
Section: International Journal Of Medical and Biomedical Studies (Ijmmentioning
confidence: 47%
“…(12) The gold standard diagnostic test of BTB is detection of AFB by ZN staining by microscopy or by solid or liquid culture accounting for 12% positivity by ZN staining and 26% by culture is in various studies and but we found it to be 6% and 15.8% respectively due to paucibacillary samples. (6,9).…”
Section: International Journal Of Medical and Biomedical Studies (Ijmmentioning
confidence: 99%
See 2 more Smart Citations
“…2 In this case, the patient had no typical clinical manifestations of tuberculosis and was eventually diagnosed by Xpert MTB/RIF; therefore, it is important to remember that breast tuberculosis is still present and should be suspected particularly in PLHIV. 3,4 Differential diagnosis most often involves carcinoma of the breast but may include benign neoplasms, pyogenic abscess, fungal infection, actinomycosis, fat necrosis, and sarcoidosis. 5 Imaging examination of the breast may not distinguish between benign and malignant lesions, so biopsy of the pathological tissue is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%